2017
DOI: 10.5539/hes.v7n2p67
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Geogebra on Students’ Conceptual and Procedural Knowledge: The Case of Applications of Derivative

Abstract: Integrating the properties of computer algebra systems and dynamic geometry environments, Geogebra became an effective and powerful tool for teaching and learning mathematics. One of the reasons that teachers use Geogebra in mathematics classrooms is to make students learn mathematics meaningfully and conceptually. From this perspective, the purpose of this study was to investigate whether instruction with Geogebra has effect on students' achievements regarding their conceptual and procedural knowledge on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 17 publications
(40 reference statements)
6
11
1
6
Order By: Relevance
“…The attention and care are given to the intervention over a semester could too. Given learners' achievement towards conceptual knowledge, the finding of this study with t(148)=11.576 and effect size value eta squared=.48, was by far different from that of similar or other related reviewed literature, for instance, (Ocal, 2017) with t(53)=2.786. The same reason holds that the finding of this study was also by far different from Oktaviyanthi and Supriani (2015); Zulnaidi and Zamri (2017); Zulnaidi and Zakaria (2012) on learners' conceptual knowledge achievement score.…”
Section: Discussioncontrasting
confidence: 99%
“…The attention and care are given to the intervention over a semester could too. Given learners' achievement towards conceptual knowledge, the finding of this study with t(148)=11.576 and effect size value eta squared=.48, was by far different from that of similar or other related reviewed literature, for instance, (Ocal, 2017) with t(53)=2.786. The same reason holds that the finding of this study was also by far different from Oktaviyanthi and Supriani (2015); Zulnaidi and Zamri (2017); Zulnaidi and Zakaria (2012) on learners' conceptual knowledge achievement score.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, from the result of this research, it can be concluded learning mathematics on circle object using Geogebra is more effective in improving creative thinking ability and visual thinking ability than the conventional methods [32][33].They said the use of Geogebra dynamic geometry software has the potential to improve and enhance students' critical knowledge and skills, creative and innovative thinking towards supporting problem-based learning as an approach in 21st century learning [34][35].…”
Section: Discussionmentioning
confidence: 88%
“…The result of study, significant differecence were found between groups' academic performances in favor of experimental group. In the literature, there are studies,regarding traditional instruction is not enou gh and GeoGebra-assisted instruction is positive impact on the learning process (Dikovic, 2009;Shadaan & Leong, 2013) increases the level of academic performance (Saha, Ayub & Tarmizi, 2010;Gómez-Chacón & Escribano, 2011;Zengin, Furkan & Kutluca, 2012;Güven & Yılmaz, 2012;Tatar, Kağızmanlı & Akkaya, 2014;Kan, 2014;Aydos,2015;Acar, 2015;Bhagat & Chang, 2015;Ünlütürk-Akçakın, 2016;Kepçeoğlu & Yavuz, 2017;Ocal, 2017;Çekmez & Baki, 2018) and makes learning easier (Taş, 2010;Reis & Özdemir, 2010). In this study, significant differecence were found between groups' geometric and ovarall performances in favor of experimental group however there is no significant difference between the experimental and control groups with respect to algebraic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Bu bulgu, GeoGebra destekli öğretimin öğretmen adaylarının akademik performanslarını geleneksel öğretime göre daha fazla geliştirdiği sonucunu ortaya koymaktadır. Literatürde geleneksel öğretimle gerçekleştirilen matematik öğretimin yeterli olmadığını GeoGebra destekli öğretimin öğrenme sürecine olumlu etkilerinin olduğunu (Dikovic, 2009;Shadaan ve Leong, 2013), akademik performans düzeyini artırdığını (Saha, Ayub ve Tarmizi, 2010;Gómez-Chacón ve Escribano, 2011;Zengin, Furkan ve Kutluca, 2012;Güven ve Yılmaz, 2012;Tatar, Kağızmanlı ve Akkaya, 2014;Kan, 2014;Aydos,2015;Acar, 2015;Bhagat ve Chang, 2015;Ünlütürk-Akçakın, 2016;Kepçeoğlu ve Yavuz, 2017;Ocal, 2017;Çekmez ve Baki, 2018) ve öğrenmeyi kolaylaştırdığını (Taş, 2010;Reis ve Özdemir, 2010) gösteren araştırmalar bulunmaktadır. Ayrıca, araştırmanın bulguları, GeoGebra destekli öğretimin cebirsel performans bağlamında gruplar arasında bir farklılık oluşturmadığını ancak geometrik performansı ve genel performansı artırdığını göstermektedir.…”
Section: Veri Toplama Araçlarıunclassified
See 1 more Smart Citation